Southeast Kansas Crop Production Summary - 2019 - G. F. Sassenrath; L. Mengarelli; J. Lingenfelser; X. Lin; E. Adee (Kansas Agricultural Experiment Station Research Reports, 2020)
This is a summary of the crop production conditions in southeast Kansas in 2019, and the results of the variety testing for corn, soybean, sorghum, sunflower, and wheat.
Keywords: crop production; southeast Kansas; corn; wheat; soybeans; sorghum; sunflower